Leucocyte Blood Picture in Healthy Full-term and Premature Babies During Neonatal Period - Xanthou, M. (1970)
Serial leucocyte counts were done on 15 full-term babies during the first 10 days of life and on 14 prematures during the first 30 days. In addition a single count was done on the total of 53 babies around the 96th hour of life. Absolute values of each cell type are given for each postnatal age examined. The main changes in the leucocyte counts during the neonatal period were found to be as follows: (a) An increase in polymorphonuclear neutrophils after birth, reaching a peak at 12 hours, thereafter dropping to a figure which remains fairly constant from 72 hours onwards. (b) A decrease in polymorphonuclear neutrophil precursors. (c) A drop in lymphocytes reaching a minimum at 3 days of age, and thereafter rising to a steady level at about 10 days. The mean values ± 2SD for each cell type at 96 hours of life are as follows. Polymorphonuclear neutrophils: Mean = 4100/ cu.mm., M + 2SD = 6900/cu.mm., M - 2SD = 1400/cu.mm. Eosinophils: Mean = 700/cu.mm., M + 2SD = 1900/cu.mm., M - 2SD = 200/cu.mm. Lymphocytes: Mean = 3900/cu.mm., M + 2SD = 7100/cu.mm., M - 2SD = 2200/cu.mm. Monocytes: Mean = 1000/cu.mm., M + 2SD = 1800/cu.mm., M - 2SD = 200/ cu.mm.